Pengaruh Tingkat Pendidikan, Pembangunan Infrastruktur Dan Pembangunan Real Estate Terhadap Tingkat Serapan Tenaga Kerja Di Provinsi Papua Barat Tahun 2010-2014 - Mus Mualim; Sarce Babra Awom (Pusat Penelitian Pemberdayaan Fiskal dan Ekonomi Daerah (P3FED) Universitas Papua, 2019)
This study intends to analyze the influence of education level, infrastructure sector and real estate sector on labor absorption in West Papua Province. The data used in this study are secondary data, namely labor force data in districts and cities in West Papua Province, recent diploma data aged 15 years and over in West Papua Province 2010-2014, GRDP data on the basis of the constant price of the infrastructure sector (construction, transportation and warehousing) and GRDP data on the basis of the constant price of the real estate sector. Using panel data regression analysis, the results of this study indicate that the level of education and the infrastructure sector have a positive but not significant effect on labor absorption rates. Furthermore, the real estate sector has a positive and significant effect on labor absorption rates in West Papua Province